ビスホスホネート投与患者の抜歯後BRONJ発生に関する多施設共同前向き研究 - 藤盛, 真樹; 榊原, 典幸; 三澤, 肇; 牧野, 修治郎; 針谷, 靖史; 宮手, 浩樹; 柴山, 尚大; 谷村, 晶広; 工藤, 章裕; 鳥谷部, 純行; 角, 伸博; 山下, 徹郎; et al. (日本口腔外科学会雑誌, 2022)
Tooth extraction is reported as the main trigger of bisphosphonate (BP) -related osteonecrosis of the jaw (BRONJ). A method to prevent BRONJ has not been scientifically proven. The American Association of Oral and Maxillofacial Surgeons (AAOMS) differs from the International Task Force on Osteonecrosis of the Jaw with regard to the prevention of BRONJ via prophylactic withdrawal before tooth extraction. We performed a multicenter prospective study regarding the development of BRONJ after tooth extraction in BP-treated patients for the purpose of determining factors associated with the frequency of BRONJ. We extracted teeth from patients with a history of current or prior treatment with BP preparations; teeth were extracted using a common treatment protocol. The presence or absence of BRONJ and adverse events were evaluated. A total of 1,323 cases were targeted for this study; 2,371 teeth were extracted. The overall incidence of BRONJ was 1.74%; in the prophylactic withdrawal group it was 1.73%, whereas in the prophylactic non-withdrawal group it was 1.75%. Factors associated with the onset of BRONJ were sex, preparation adaptation classification, oral hygiene state, site of tooth extraction, and Denosumab usage. From analysis that considered the effect of confounding using the propensity score, prophylactic BP withdrawal did not result in a reduction of BRONJ (onset odds ratio with withdrawal: 1.13, 95%CI 0.36-3.57).